PENGARUH KEBIJAKAN SPIN-OFF DAN PERTUMBUHAN EKONOMI TERHADAP KESEHATAN BANK UMUM SYARIAH - Nawasiah, Nana; Alkaf, Fatima Tuzzahara (Economic Faculty, Attahiriyah Islamic University, 2020)
Purpose- This study aims to determine the effect of the spin-off policy and economic growth on bank health both partially and simultaneously.Design/methodology/approach- This research is a quantitative and verification research that is to do calculations on financial data obtained to solve existing problems in accordance with the objectives research. Secondary data over 2014-2018 obtained from the bank's annual report. The analysis was carried out by applying Multiple Linear Regression models using the SPSS program on 6 banks based on purposive sampling.Findings- Estimation results show that during the 2014-2018 study period, spin-off policy and GDP had no influence on the health of banks both in terms of capital and financing/problem loans. But simultaneously, in terms of capital/capital and financing/credit problems show that the independent variable has an influence on the dependent variable.Implications-The scope of this research only covers 6 Sharia Commercial Banks namely, PT Bank BNI Syariah, PT Bank Central Asia Syariah, PT Bank Syariah Mandiri, PT Bank BRI Syariah, PT Bank BTPN Syariah, and PT Bank Bukopin Syariah. Thus, the observation can be extended by making comparisons with other Sharia Commercial Banks that have conducted spin-off.Keywords: Health of Sharia Commercial Bank, Spin-Off Policy, Economic Growth